THE CORRELATION BETWEEN SELF-EFFICACY, SOCIAL SKILLS, AND ACHIEVEMENT INDEX OF ELEMENTARY SCHOOL TEACHERS' CANDIDATES - Yuliyanto, Aan; Basit, Rifqi Abdul; Priatna, Yundara Ulfa; Sujana, Atep; Putri, Hafiziani Eka; Muqodas, Idat (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
The intensity of online learning impacts students' self-confidence in solving problems, their ability to interact with other people, and even their achievements. This study aims to examine the correlation between self-efficacy, social skills, and students’ grade point average (GPA) through a correlational method with an explanatory design and using questionnaires and interview sheets. The sample was taken randomly, totaling 55 students of the elementary school teacher education program at one of the state universities in Purwakarta, Indonesia. The findings show a correlation between student self-efficacy and the Grade Point Average; there is a correlation between social skills and GPA. When self-efficacy and social skills separately increase, the GPA will increase and vice versa. In addition, there is no correlation between student self-efficacy and social skills. Moreover, there is no correlation between self-efficacy and social skills simultaneously with the GPA. When self-efficacy and social skills increased, it was not confident that the GPA would increase. Self-efficacy and social skills have an impact on one's achievement. Therefore, the interactive and easily accessible online learning development is needed. Abstrak: Intensitas pembelajaran online memberi dampak pada keyakinan diri mahasiswa dalam memecahkan masalah, kemampuanya dalam berinteraksi dengan orang lain, bahkan prestasinya. Penelitian ini bermaksud untuk mengkaji hubungan antara efikasi diri, keterampilan sosial, dan Indeks Prestasi Kumulatif (IPK) siswa melalui metode korelasional dengan desain eksplanatori dan menggunakan instrumen angket dan lembar wawancara. Sampel diambil secara acak yang berjumlah 55 mahasiswa program studi pendidikan guru sekolah dasar di salah satu perguruan tinggi negeri di Purwakarta, Indonesia. Temuan menunjukkan adanya hubungan antara self-efficacy mahasiswa dengan Indeks Prestasi Kumulatif, adanya hubungan antara keterampilan sosial mahasiswa dengan Indeks Prestasi Kumulatif, sehingga ketika self-efficacy dan keterampilan sosial mahasiswa secara terpisah meningkat maka indeks prestasi kumulatif mahasiswa akan meningkat dan sebaliknya. Selain itu tidak adanya hubungan antara self-efficacy mahasiswa dengan keterampilan sosial sehingga ketika self-efficacy meningkat atau menurun maka tidak dapat dipastikan keterampilan akan menunjukkan hasil yang sama. Serta ditemukan tidak adanya hubungan antara self-efficacy dan keterampilan sosial secara bersamaan dengan Indeks Prestasi Kumulatif mahasiswa. Self-efficacy dan keterampilan sosial berdampak pada prestasi seseorang. Oleh karena itu, pengembangan pembelajaran online interaktif dan akses mudah diperlukan.